Production of Load Bearing Concrete Masonry Units (blocks) From Green Concrete Containing Plastic Waste and Nano Silica Sand Powder - Mohammed Fadhil Qasim; ZENA K. ABBAS; SOHAIR Kadhem Abed (Journal of Engineering, 2022)
Industrial development has recently increased, including that of plastic industries. Since plastic has a very long analytical life, it will cause environmental pollution, so studies have resorted to reusing recycled waste plastic (sustainable plastic) to produce environmentally friendly concrete (green concrete). In this research, producing environmentally friendly load-bearing concrete masonry units (blocks) was considered where five concrete mixtures were compressed at the blocks producing machine. The cement content reduced from 400 kg/m3 (B-400) to 300 kg/m3 (B-300) then to 200 kg/m3 (B-200). While (B-380) was produced using 380 kg/m3 cement and 20 kg/m3 nano-silica sand powder, and 10% plastic waste instead of coarse aggregate. Finally (B-285) included 285  kg/m3 cement and  15 kg/m3 nano silica sand powder and 10% plastic waste replacement for coarse aggregate. All production of concrete masonry unit types. According to IQS 1077 /1987, except (B-200) and (B-285) type B. When increasing the curing age from 14 to 28 days, blocks (B-285and B-380) change from type B to A. The compressive strength of the types (B-400, B-300, B-200, B-380, and B-285) was (9.65, 7.11, 5.35, 6.57, and 5.86) MPa, respectively, at 14 days and (11.98, 9.33, 6.84, 8.62 and 7.64) MPa respectively at 28 days.